The Effect of the Combination of PLA, PP, and ABS Filaments on Flexural Strength in FDM 3D Printing - Mahros Darsin; Izharudin Ahmad; Intan Hardiatama; Agus Triono; I Made Ivan Wiyarta Cakra Sujana (Journal of Information Technology, computer science and Electrical Engineering, 2024)
3D printing of fused deposition modeling (FDM) technique is one of the most widely used nowadays. One disadvantage of this method is that the printed product has low strength to the fact that the product is developed layer by layer. This research aims to combine PLA, PP, and ABS and determine which results in the highest flexural strength. A Cartesian 3D printer printed specimens according to the ASTM D790 standard. Then, specimens were tested using a universal testing machine. An optic microscope was used to observe the fracture area. The results showed that the combination of PLA-ABS increased flexural strength up to 33.12 MPa. While PLA-PP, PLA-PP-ABS and PP-ABS resulted in a flexural strength of less than half PLA-ABS one, they were 14.90, 14.59 and 12.10 MPa, respectively. All alloy combinations except PLA-ABS were delaminated during the bending test. Delamination causes a decrease in the flexural strength of a specimen.